Obsession to Finding Parents in Kirsten Sheridan August Rush Movie (2007): An Individual Psychological Approach - Nurfadlillah, Siti (2012)
The study is to reveal how the obsession of finding parents of the major character influences his personality. The objective of this study is to analyze the movie based on structural analysis and describing obsession of August Rush in the story based on individual psychological approach. This study is a qualitative study. The object of the study is August Rush movie directed by Kirsten Sheridan. The primary data source is August Rush movie itself and secondary data sources are the other sources related to the movie. The method of data collection is documentation research. The technique of data analysis is descriptive analysis. Based on the analysis, there are two conclusions. First, from the structural analysis it shows that each element is interrelated to each other and forms unity. Second, from the individual psychological analysis, it shows that obsession can make him survive and strive to find his parent. So, he must get his obsession in right way.